Relationships between psychoevolutionary fear of evaluation, cognitive distortions, and social anxiety symptoms: A preliminary structural equation model. (16th July 2018) - Cook, Sarina I.; Meyer, Denny; Knowles, Simon R.
Abstract : Social anxiety disorder is a mental health condition that affects 4.7% of Australians each year. The complex interplay between psychoevolutionary and cognitive models has become the focus of research in recent years, particularly with the development of the bivalent fear of evaluation model (i.e., negative and positive evaluation fears). The present study aimed to test a model of social anxiety symptoms using structural equation modelling, integrating previously fragmented evidence. A sample of 255 participants (75.3% female; M age = 31.9, SD = 10.3) undertook an online survey, including Social Phobia Scale, Brief Fear of Negative Evaluation—Straightforward, Fear of Positive Evaluation, Concerns of Social Reprisal, and Disqualifications of Positive Social Outcomes measures. The hypothesised model for social anxiety symptoms described the data reasonably well ( χ 2 (1) = 4.917, p = .027, CFI = .995, GFI = .992, SRMR = .017), explaining 57.1% of social anxiety variance. Study hypotheses were supported with bivalent fear of evaluation accounting for unique variance in cognitive distortions, which in turn accounted for unique variation in social anxiety symptoms. Effect sizes indicate bivalent fears of evaluation and disqualification of positive social outcomes as important predictors of social anxiety symptoms. Although replication in a clinical cohort and experimental confirmation are needed, the findings suggest a focus on disqualification of positive social outcomes to alleviate social anxiety symptoms.